Limitations, Progress and Prospects of Application of Biotechnological Approaches in Improvement of Prosopis: An Important Genus of the Arid Regions - Kalia, Rajwant K; Krishnan, P R. Ratha; Tewari, J C (Annals of Arid Zone, 2016)
Introduction and selection of fast-growing exotic tree and shrub species into the arid regions of Indian subcontinent is imperative to ensure a sustained livelihood under harsh agro-climatic conditions in the region. Large scale mortality of perennials, mechanized agriculture, industrialization and population explosion, increased demand of fuel and fodder, and cutting of trees without adequate reforestation has also fueled the concern for saving such fragile ecosystems from degradation. Prosopis, a multipurpose, leguminous, nitrogen fixing genus encompassing approximately 45 species of trees and shrubs remains one of the most widely accepted genera in the arid regions as many of the species of the genus are highly adapted for survival in arid, semi-arid and usar lands. However, there is an urgent need to modify and improve the undesirable features like thorniness, bushy architecture, slow growth rate and high alkaloid content in leaves of important Prosopis spp. by developing tailored genotypes suitable for plantation and rapid growth in these dry regions. Limited progress has been made for improvement of the genus through conventional breeding programs due to lack of identified superior parental lines, lack of knowledge about extent of hybridization possible between species, genetic linkage maps and QTL linkage maps. Conventional propagation methods i.e., through seeds and rooting of cuttings are in place, but have limitations for development of genetically uniform planting material on a larger scale. Therefore, application of modern tools of biotechnology need to be standardized for harnessing maximum benefits from this plant. Improvement of this genus through genetic transformation requires an efficient regeneration system, which is yet to be perfected for large scale production of planting material. Genetic diversity studies, taxonomic delineation of species and subspecies and also the breeding programs can be more robustly addressed using molecular markers. An attempt has been made to review the need and the scope of genetic improvement of this important genus using modern tools of biotechnology. Key words: Fabaceae, Prosopis, micropropagation, molecular markers, tree improvement